ANALISIS YURIDIS PENGENAAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) ATAS INBRENG PENDIRIAN PERSEROAN TERBATAS - AINI HALIM (PREMISE LAW JURNAL, 2015)
The establishment of a corporation requires that every person who wants to set up a corporation has to be a stockholder at the time it is established. The capital payment for the stock can use in a different form (inbreng) such as a plot of land and/or a building. The payment of land and/or building to the stock is a the transferring of the rights for land and/or building use from an individual to the corporation as a capital participation in the corporation. BPHTB is levied to the payment (inbreng). The result of the research showed that inbreng must be attached in the establishment certificate and was assessed by professional assessors who do not affiliate with the Corporation; the result was announced in newspapers. A Corporation is not allowed to own land in ownership status. It is recommended that socialization in the procedures of paying BPHTB and filling out SSPD-BPHTB since people’s awareness of their duty to pay for BPHTB is still very limited. Therefore, they need help from PPAT in filling out SSPD-BPHTB and paying for BPHTB directly to the appointed Bank. Keywords: Establishment of Corporation, Land Inbreng, BPHTB